(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
The main aim of this study is to investigate the effect of tannery effluents on the Dhaleshwari River water near Savar, Dhaka. The physicochemical properties analyzed included pH, electrical conductivity (EC), dissolved oxygen (DO), total dissolved solids (TDS), total hardness (TH), chloride ion (Cl⁻), sodium ion (Na⁺), potassium ion (K⁺), chromium (Cr), lead (Pb), and cadmium (Cd) to determine the current pollution status of the river. The pH was 5.50-7.64. The EC was 207.40-258.60 μScm-1, indicating standard ionic species in the water. TDS levels were 149.00-177.00 mgL-1. Na⁺ and K⁺, determined using a flame photometer, ranged from 28.49-34.48 mgL-1 and 2.92-3.94 mgL-1, respectively. Cl- content, measured by titrimetric method, ranged from 8.50-30.23 mgL-1. Heavy metals were analyzed using an Atomic Absorption Spectrophotometer (AAS), revealing Pb levels from below detection limit (BDL) to 0.07 mg/L and Cr levels from BDL to 0.015 mg/L, while Cd was BDL in all samples. The microbial analysis detected only coliform bacteria, including E. coli and Salmonella sp. The study concludes that the Dhaleshwari River shows evidence of pollution from tannery effluents, particularly in terms of heavy metals and microbial contamination, although some physicochemical properties remain within standard levels. J. Bangladesh Acad. Sci. 49(1); 45-55: June 2025